Osteoporosis and Spine Surgery: A Critical Analysis Review. Issue 6 (June 2020) - Diebo, Bassel G.; Sheikh, Basel; Freilich, Michael; Shah, Neil V.; Redfern, James A.I.; Tarabichi, Saad; Shepherd, Elian M.; Lafage, Renaud; Passias, Peter G.; Najjar, Salem; Schwab, Frank J.; Lafage, Virginie; et al.
Abstract : Despite being part of the aging process, early and adequate management of osteoporosis mitigates adverse outcomes associated with low bone mineral density. Although the health-care burden of osteoporosis is on the rise, screening and management of osteoporosis are not yet an integral part of preoperative patient evaluation in spine surgery. Patients with osteoporosis should undergo multidisciplinary evaluation and management, including lifestyle modifications and initiation of multiple therapeutic modalities. Integrating osteoporosis in preoperative optimization and surgical planning for patients undergoing spine surgery has the potential to mitigate osteoporosis-related postoperative complications.